PERAN PEKERJA SOSIAL DALAM MENANGANI ANAK KORBAN TINDAK KEKERASAN SEKSUAL (Fakultas Dakwah dan Komunikasi, 2020)
The journal that was created aims to describe the roles and efforts made by social workers in dealing with child victims of sexual violence. The explanation of this article is obtained from the results of literature studies from various readings such as journals, books, and direct interviews with social workers. The increase in sexual violence against children shows the importance of handling child victims of sexual violence. The results of the analysis show that the role of the Social Worker determines the success of the recovery or the provision of services running well. With the role of social workers, child victims of sexual violence can return to functioning socially.